Spontaneous Heterotopic Pregnancy: A Case Report - Sujata Maharjan; Rumina Malla; Babita Chaudhary; Piyush Shrestha; Lakpa Dolma Lama (Journal of Nepal Medical Association, 2023)
Spontaneous heterotopic pregnancy is a rare clinical condition which is a potentially dangerous condition where at least two pregnancies are present simultaneously at different implantation sites and only one is located in the intrauterine cavity. It is a life-threatening condition with an incidence estimated as 1 in 30,000 natural conceptions. Being rare it’s challenging to diagnose such conditions due to complex clinical and laboratory findings. In view of the survival of maternal as well as intrauterine pregnancy, a high index of suspicion leading to timely diagnosis and appropriate intervention is needed. We are reporting a case of a 28-year-old female with heterotopic pregnancy at 8 weeks of gestation following natural conception diagnosed by ultrasound and managed successfully by laparoscopic salpingectomy. Intrauterine pregnancy was continued normally till term with no complications. Hence, with timely diagnosis and early intervention, maternal and fetal survival is possible.